2015
DOI: 10.1002/oby.21144
|View full text |Cite
|
Sign up to set email alerts
|

Cthrc1 controls adipose tissue formation, body composition, and physical activity

Abstract: Objective This study investigated the effects of loss of Cthrc1 on adipogenesis, body composition, metabolism, physical activity and muscle physiology. Methods Complete metabolic and activity monitoring as well as grip strength measurements and muscle myography were performed in Cthrc1 null and wildtype mice. Results Compared to wildtypes, Cthrc1 null mice had similar body weights but significantly reduced energy expenditure, decreased lean mass and increased fat mass, especially visceral fat. In vitro stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…CREB is a well-documented transcription factor involved in adipocyte differentiation and lipid metabolism. Previous study has shown collagen triple helix repeat containing 1 (Cthrc1) inhibits adipocyte differentiation by inhibiting PPARγ signaling and activating CREB [ 32 ], which is consistent with our findings CREB as a negative regulator in ColXV promoted adipocyte differentiation. Although some reports indicated that CREB participates in adipogenesis via positive transcriptional regulating C/EBPβ and PPARγ at early state [ 33 , 34 ], we found CREB suppressed adipocyte differentiation dependent on ColXV.…”
Section: Discussionsupporting
confidence: 93%
“…CREB is a well-documented transcription factor involved in adipocyte differentiation and lipid metabolism. Previous study has shown collagen triple helix repeat containing 1 (Cthrc1) inhibits adipocyte differentiation by inhibiting PPARγ signaling and activating CREB [ 32 ], which is consistent with our findings CREB as a negative regulator in ColXV promoted adipocyte differentiation. Although some reports indicated that CREB participates in adipogenesis via positive transcriptional regulating C/EBPβ and PPARγ at early state [ 33 , 34 ], we found CREB suppressed adipocyte differentiation dependent on ColXV.…”
Section: Discussionsupporting
confidence: 93%
“…) and adipose tissue metabolism (Stohn et al. ). The exact function of synaptotagmin 16, which is the product of SYT16 (Fukuda ), and which was down‐regulated in healing gingiva, remains unknown; there are no previous reports of SYT16 expression in the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Cthrc1 encodes for a secreted protein that was first identified to increase bone mass by regulating osteoblast proliferation and differentiation [ 75 ]. Recent studies also show that this factor has a metabolic function, as whole-body Cthrc1 deficiency will promote liver steatosis and increased subcutaneous fat mass [ 76 , 77 ]. Another example is biglycan (encoded by Bgn ) that is induced 11-fold by Akt1 in muscle.…”
Section: Discussionmentioning
confidence: 99%